Establishment of Reporter Lines for Detecting Fragile X Mental Retardation (FMR1) Gene Reactivation in Human Neural Cells. (27th July 2016) - Li, Meng; Zhao, Huashan; Ananiev, Gene E.; Musser, Michael T.; Ness, Kathryn H.; Maglaque, Dianne L.; Saha, Krishanu; Bhattacharyya, Anita; Zhao, Xinyu
Abstract : Human patient-derived induced pluripotent stem cells (hiPSCs) provide unique opportunities for disease modeling and drug development. However, adapting hiPSCs or their differentiated progenies to high throughput assays for phenotyping or drug screening has been challenging. Fragile X syndrome (FXS) is the most common inherited cause of intellectual disability and a major genetic cause of autism. FXS is caused by mutational trinucleotide expansion in the FMR1 gene leading to hypermethylation and gene silencing. One potential therapeutic strategy is to reactivate the silenced FMR1 gene, which has been attempted using both candidate chemicals and cell-based screening. However, molecules that effectively reactivate the silenced FMR1 gene are yet to be identified; therefore, a high throughput unbiased screen is needed. Here we demonstrate the creation of a robust FMR1 -Nluc reporter hiPSC line by knocking in a Nano luciferase (Nluc) gene into the endogenous human FMR1 gene using the CRISPR/Cas9 genome editing method. We confirmed that luciferase activities faithfully report FMR1 gene expression levels and showed that neural progenitor cells derived from this line could be optimized for high throughput screening. The FMR1 -Nluc reporter line is a good resource for drug screening as well as for testing potential genetic reactivation strategies. In addition, our data provide valuable information for the generation of knockin human iPSC reporter lines for disease modeling, drug screening, and mechanistic studies.